Optimizing 3D printing performance of acrylonitrile‐butadiene‐styrene composites with cellulose nanocrystals/silica nanohybrids. Issue 7 (30th April 2019) - Huang, Bai; He, Hui; Meng, Shuna; Jia, Yunchao
Abstract: The preparation of 3D printed products with excellent comprehensive performance is still receiving much attention. Cellulose, the most abundant and green natural polymer, was used in this study to fabricate polymeric composites used for 3D printing. Specifically, novel cellulose nanocrystals/silica nanohybrids (CSNs) were synthesized via the sol–gel method using cellulose nanocrystals (CNCs) obtained by hydrolysis of sulfuric acid as raw materials, and the thermostability was significantly improved due to the adsorption of silica (SiO2 ) on the surface of the CNCs via hydrogen bonding and covalent bonds. Subsequently, the CSNs were used in fused deposition modeling (FDM) with acrylonitrile‐butadiene‐styrene (ABS) as the matrix. Unlike ABS/CNC product which shows obvious yellowing, the ABS/CSN product shows a smooth undefiled surface, demonstrating their excellent applicability to high temperature FDM molding. Further, the effect of different silane coupling agents on the mechanical properties was compared and organically modified CSNs (oCSNs) were prepared using KH570 to optimize the dispersion of the filler and the interaction with the matrix. Satisfactorily, the addition of organically modified oCSNs not only does not degrade the fluidity but it also eliminates the warpage of FDM products and improves both layer adhesion and mechanical properties. This study provides a pioneering strategy for the thermal processing applications of CNCs and the modification of FDM products. © 2019 Society of Chemical Industry Abstract : Novel cellulose nanocrystals/silica nanohybrids were synthesized via the sol–gel method and successfully used in high temperature fused deposition molding, improving the comprehensive performance of acrylonitrile‐butadiene‐styrene products.